Transcriptional Circuits Regulating Developmental Processes in Candida albicans - Rodriguez, Diana L.; Quail, Morgan M.; Hernday, Aaron D.; Nobile, Clarissa J. (Frontiers in Cellular and Infection Microbiology, 2020)
Candida albicans is a commensal member of the human microbiota that colonizes multiple niches in the body including the skin, oral cavity, and gastrointestinal and genitourinary tracts of healthy individuals. It is also the most common human fungal pathogen isolated from patients in clinical settings. C. albicans can cause a number of superficial and invasive infections, especially in immunocompromised individuals. The ability of C. albicans to succeed as both a commensal and a pathogen, and to thrive in a wide range of environmental niches within the host, requires sophisticated transcriptional regulatory programs that can integrate and respond to host specific environmental signals. Identifying and characterizing the transcriptional regulatory networks that control important developmental processes in C. albicans will shed new light on the strategies used by C. albicans to colonize and infect its host. Here, we discuss the transcriptional regulatory circuits controlling three major developmental processes in C. albicans: biofilm formation, the white-opaque phenotypic switch, and the commensal-pathogen transition. Each of these three circuits are tightly knit and, through our analyses, we show that they are integrated together by extensive regulatory crosstalk between the core regulators that comprise each circuit.